Pengaruh model pembelajaran concept sentence dan minat belajar terhadap keterampilan menulis narasi pada peserta didik kelas v sekolah dasar - Mulyani, Dewi; Slamet, St Y; Suharno, Suharno (Universitas Sebelas Maret, 2023)
The research aims to know the students skill of the narrative writing. The population of this study were all fifth grade students of Elementary School in Gondangrejo District in the 2018/2019 academic year with cluster random sampling technique. This study uses an experimental method with a 2x2 factorial design. Data collection was carried out using a test technique for data on narrative writing skills and non-test techniques for data on student interest in learning. Questionnaire is used on the variable of interest in learning. The data analysis technique used two-way Anava test with unequal cell frequencies. The results show that the narrative writing skills of students who are taught the Concept Sentence learning model are better than students who are taught the Cooperative Integrated Reading and Composition (CIRC) learning model (FA = 10,77 ˃ F(0,05;1;44) = 4,06), high learning interest has a better effect on narrative writing skills than low learning interest (FB = 32,58 ˃ F(0,05;1;44) = 4,06); and there is no interaction effect between learning model and interest in learning on narrative writing skills (FAB = 1,82 ˃ F(0,05;1;44) = 4,06).